Arima Model for Forecasting Coffee Productivity in West Sumatra, Indonesia - Mutiara, Vonny Indah; Khairati, Rusda; Putri, Dwi Nur'aini (Indonesian Journal of Applied Research (IJAR), 2025)
As the 10th highest coffee-producing region in Indonesia, West Sumatra played a significant role in the country's coffee sector. Coffee productivity in West Sumatra had been fluctuating; therefore, accurate productivity forecasting was essential for effective coffee farm management, resource allocation, and market stability. This study aimed to identify the best forecasting model for predicting coffee productivity in West Sumatra from 2024 to 2028. The research method used was the descriptive analysis method, applying a time series forecasting approach. The data used in this study were historical records of coffee productivity in West Sumatra for the past 24 years. The data were annual figures from 2000 to 2023. The results showed that ARIMA (1,3,0) was the most suitable, with a Mean Absolute Percentage Error (MAPE) below 50%. This indicated a declining trend in coffee productivity over the forecast period. The projected productivity values (tons per hectare) were 1.000 in 2024, 0.6266 in 2025, 0.6125 in 2026, 0.0538 in 2027, and -0.1709 in 2028. The pattern of minor variations suggested that the ARIMA (1,3,0) model reflected an unstable and downward trend in coffee productivity.